Interest and preferences for contingency management design among addiction treatment clientele. (3rd May 2016) - Hartzler, Bryan; Garrett, Sharon
ABSTRACT: Background : Despite strong support for its efficacy, debates persist about how dissemination of contingency management is most effectively undertaken. Currently-promoted contingency management methods are empirically-validated, yet their congruence with interests and preferences of addiction treatment clientele is unknown. Such client input is a foundational support for evidence-based clinical practice. Objective : This study documented interest in incentives and preferences for fixed-ratio vs. variable-ratio and immediate vs. distal distribution of earned incentives among clients enrolled at three community programs affiliated with the National Institute on Drug Abuse Clinical Trials Network. Methods : This multi-site study included anonymous survey completion by an aggregate sample of 358 treatment enrollees. Analyses first ruled out site differences in survey responses, and then tested age and gender as influences on client interest in financial incentives, and preferences for fixed-ratio vs. variable-ratio reinforcement and immediate vs. distal incentive distribution. Results : Interest in different types of $50 incentives (i.e. retail vouchers, transportation vouchers, cash) was highly inter-correlated, with a mean sample rating of 3.49 (0.83) on a five-point scale. While consistent across client gender, age was an inverse predictor of client interest in incentives. A majority of clients stated preference for fixed-ratio incentive magnitude and distal incentive distribution (67% and 63%, respectively), with these preferences voiced by a larger proportion of females. Conclusion : Sample preferences contradict currently-promoted contingency management design features. Future efforts to disseminate contingency management may be more successful if flexibly undertaken in a manner that incorporates the interests and preferences of local client populations.